Analisis Semantik Toshihiko Izutsu tentang Makna “Basyar” dalam al-Quran dan hubungannya dengan Pendidikan: Kajian Ilmu Dilalah - Mohammad Zainal Hamdy; Miftahul Huda; Wiwik Prasetiyo Ningsih; Munirah Munirah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Semantic Studies or ilm dilalah is one of the studies in Arabic language that is used to understand the meaning or meaning of a word, it is also said ilm ma'na, Toshihiko Izutsu is an expert in semantic studies who has his own concept in studying a meaning, especially meaning in the Koran. This study aims to find the meaning or concept of basyar in the Koran using Toshihiko Izutsu's theory, then look for the relationship between this concept and Islamic Education. The research method used is literature review whose data comes from books or references. The results of this study indicate that basyar has 3 conceptual meanings namely Creation, Biology, and Prophethood. And Islamic Education plays a role in regulating and educating basyar from a biological aspect so that they are able to become knowledgeable, faithful and pious human beings like the prophets